Picard Groups of Algebraic Groups and an Affineness Criterion - Rosengarten, Zev (Comptes Rendus. Mathématique)
We prove that an algebraic group over a field $k$ is affine precisely when its Picard group is torsion, and show that in this case the Picard group is finite when $k$ is perfect, and the product of a finite group of order prime to $p$ and a $p$-primary group of finite exponent when $k$ is imperfect of characteristic $p$.